Efficiency of energy actions under the PBE-edic and its impacts on Brazil us last 11 years 1 - Araújo , Larissa; Rodrigue, Clear; Pedrin, Aldomar (Seven Editora, 2023)
This paper describes the national impact of National investments on the PBE-Edifica program context, in the last 11 years. A survey was carried out with the R3E integrant, INMETRO, ELETROBRAS, and FISP, organized in main actions of building energy efficiency, public investments in building energy efficiency, energy labelling offices, and buildings labelled. As a result, 1126 professionals were trained and buildings all around the country were labelled, made possible by the labelling offices and laboratories sponsored by ELETROBRAS. In conclusion, such a legacy was only possible due to the State investments, by ELETROBRAS, considering that it is a new market and affected by the economy. DOI: 10.56238/pacfdnsv1-062